Treatment outcomes of patients with MDR-TB in Nepal on a current programmatic standardised regimen: retrospective single-centre study. Issue 1 (12th August 2020) - Ghimire, Samiksha; Karki, Samriddhi; Maharjan, Bhagwan; Kosterink, Jos G W; Touw, Daan J; van der Werf, Tjip S; Shrestha, Bhabana; Alffenaar, Jan-Willem
Abstract : Objectives: The objectives of this study were to evaluate treatment in patients on current programmatic multidrug-resistant tuberculosis (MDR-TB) regimen and verify eligibility for the 9-month regimen and therapeutic drug monitoring (TDM). Methods: We performed a retrospective chart review of patients with MDR-TB receiving standardised regimen at the German Nepal TB Project Clinic, Nepal, between 2014 and 2016. Eligibility for the 9-month regimen and indications for TDM were evaluated. Results: Out of 107 available patients' medical records, 98 were included. In this centre, the MDR-TB treatment success rates were 69.0% in 2015, 86.6% in 2016 and 86.5% in 2017. The median time to sputum smear conversion was 60 days (60–90 IQR ) and culture conversion was 60 days (60–90 IQR ). Observed side effects did not impact treatment outcomes. No difference in treatment success rates was observed between patients with predisposing risk factors and those without. Only 49% (36/74) of patients were eligible for the 9-month regimen and 23 patients for TDM according to American Thoracic Society guideline criteria. Conclusions: Nepalese patients with MDR-TB on ambulatory care had good treatment outcome after programmatic treatment. Implementation of the new WHO oral MDR-TB treatment regimen may further improve treatment results. The 9-month regimen and TDM should be considered as part of programmatic care.